2017
DOI: 10.1016/j.ecoinf.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Towards automatic wild animal monitoring: Identification of animal species in camera-trap images using very deep convolutional neural networks

Abstract: Abstract. Non intrusive monitoring of animals in the wild is possible using camera trapping framework, which uses cameras triggered by sensors to take a burst of images of animals in their habitat. However camera trapping framework produces a high volume of data (in the order on thousands or millions of images), which must be analyzed by a human expert. In this work, a method for animal species identification in the wild using very deep convolutional neural networks is presented. Multiple versions of the Snaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 213 publications
(132 citation statements)
references
References 15 publications
3
103
0
3
Order By: Relevance
“…We surpassed the best results reported by Gomez Villa et al. () (roughly 58% as estimated from their plots) who also used the SS dataset but excluded rare species (modelling 26 species) and used transfer‐learning to train all of their models. However, contrary to our approach, they pretrained their models on the ImageNet dataset while we used transfer‐learning between camera trap projects.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…We surpassed the best results reported by Gomez Villa et al. () (roughly 58% as estimated from their plots) who also used the SS dataset but excluded rare species (modelling 26 species) and used transfer‐learning to train all of their models. However, contrary to our approach, they pretrained their models on the ImageNet dataset while we used transfer‐learning between camera trap projects.…”
Section: Discussionmentioning
confidence: 74%
“…To address these issues, automatic classification of camera trap images has been a focus of research in computer vision and machine learning. Recent advances in using techniques from deep learning have enabled researchers to improve automatic species identification significantly (Gomez Villa, Salazar, & Vargas, 2017;Norouzzadeh et al, 2018).…”
Section: Citizen Science and Camera Trap Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various approaches for similar classification programs exist for other purposes, such as facial recognition software, and it is surprising that image classification in camera trapping is still performed manually (Yu et al, 2013). A few authors have attempted to develop species recognition processes, with varying success McShea et al, 2016;Norouzzadeh et al, 2018;Villa, Salazar, & Vargas, 2017;Wang, 2014;Yu et al, 2013). Yu et al (2013), for instance, developed a mechanism that extracts the foreground (the animal) from the background, analyses the features of the object, and finally classifies the images by a linear support vector machine algorithm.…”
Section: Future Fe Ature Smentioning
confidence: 99%
“…Wang (2014) reaches similar accuracies ranging between 77% and 87%, depending on the exact classification method and dataset, while He et al (2016) reports lower levels of accuracy (34% and 38%; depending on method used). Most recently, Villa et al (2017) and Norouzzadeh et al (2018) have reported up to 98.1% and 96.6% accuracy, respectively, however, this drops significantly when incorporating an unbalanced dataset including uncommon species. Indeed, a disadvantage is that for each species, a high number of "practice"…”
Section: Future Fe Ature Smentioning
confidence: 99%